2018
DOI: 10.3390/ijms19092697
|View full text |Cite
|
Sign up to set email alerts
|

FK506 Attenuates the MRP1-Mediated Chemoresistant Phenotype in Glioblastoma Stem-Like Cells

Abstract: Poor response to current treatments for glioblastoma has been attributed to the presence of glioblastoma stem-like cells (GSCs). GSCs are able to expel antitumor drugs to the extracellular medium using the multidrug resistance-associated protein 1 (MRP1) transporter. Tacrolimus (FK506) has been identified as an MRP1 regulator in differentiated glioblastoma (GBM) cells (non-GSCs); however, the effect of FK506 on GSCs is currently unknown. The objective of the following research is to evaluate the effect of FK50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Previously, our group confirmed that A 3 AR blockage decreased the expression of the ABC transporter MRP1, which is highly expressed in GBM, promoting chemoresistance to Vincristine [9,47]. Here we show that ADA is also able to decrease MRPs activity, conferring chemosensitivity to vincristine (Figure 5).…”
Section: Discussionsupporting
confidence: 79%
“…Previously, our group confirmed that A 3 AR blockage decreased the expression of the ABC transporter MRP1, which is highly expressed in GBM, promoting chemoresistance to Vincristine [9,47]. Here we show that ADA is also able to decrease MRPs activity, conferring chemosensitivity to vincristine (Figure 5).…”
Section: Discussionsupporting
confidence: 79%
“…The antiangiogenic effect of rofecoxib makes GBM chemotherapy more effective (96). Tacrolimus endows the GBM stem-like cells chemosensitive to the MRP1 drug substrate (97). Of course, it is still controversial whether some of the drugs identified by our study are effective against GBM.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we used CMap analysis to accurately identify compounds that have been shown to have specific effects on GBM or other tumor types by comparing the different expression genes of GMB samples from 3 clusters. These compounds include the DNA synthesis inhibitor anisomycin ( 73 ), glutamate receptor antagonist amantadine ( 74 ), norepinephrine inhibitor amitriptyline ( 75 , 76 ), solute carrier family member inhibitor bumetanide ( 77 ), PPAR receptor agonist clofibrate ( 78 ), and fenofibrate ( 79 ), selective serotonin reuptake inhibitor (SSRI) fluoxetine ( 75 , 80 ), ATPase inhibitor helveticoside ( 81 , 82 ), norepinephrine reuptake inhibitor imipramine ( 75 , 76 , 83 , 84 ), opioid receptor agonist loperamide ( 85 ), phosphodiesterase inhibitor papaverine ( 86 , 87 ) and rolipram ( 88 92 ), polar auxin transport inhibitor quercetin ( 93 , 94 ), cyclooxygenase inhibitor rofecoxib ( 95 , 96 ), calcineurin inhibitor tacrolimus ( 97 ), purinergic receptor antagonist ticlopidine ( 98 , 99 ), HDAC inhibitor vorinostat ( 100 ), Rho associated kinase inhibitor Y-27632 ( 101 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…In severe hypoxia, overexpression of hypoxia-inducible factor (HIF)-2α upregulates ectonucleotidases and adenosine production in the GME. Adenosine activates GSCs by stimulating A2bR and A3R, leading to disease progression, angiogenesis, and chemoresistance [ 124 , 125 ] ( Figure 1 ). Adenosine signaling via A3R on GSCs converts them to endothelial cells and increases tumor angiogenesis [ 56 , 103 ].…”
Section: Adenosinergic Pathway In the Glioblastoma Immunopathogenementioning
confidence: 99%